Sistema de proteção adaptativa aplicado a redes de distribuição e microrredes em média tensão - Sampaio, Felipe Carvalho (2019)
The demand for renewable and clean energy sources rose new electrical systems concepts, as distributed generation and microgrids. Although they bring many benefits for the electrical system, distributed generation and microgrids cause huge impacts in the operation of electrical distribution systems, being the impact on protection system one of the most relevant. This work presents an adaptive protection system to mitigate the microgrid operation impact on protection system. The system is applied to directional overcurrent protection relays and propose a new metaheuristic for optimal settings calculation, the Fuzzy-Adaptive Directional Bat Algorithm (FDBA). The algorithm is validated using the data of three benchmark grids: 3-bus, 9-bus and 30-bus grids. The proposed algorithm performance is compared against the performance of Genetic Algorithm, Particle Swarm Optimization, Differential Evolution, Bat Algorithm and Directional Bat Algorithm. The results demonstrate that FDBA presented high convergence speed, low discoordination, high robustness and acceptable computational burden. The adaptive protection system was tested in a microgrid under different scenarios of grid topology, distributed generation connection and grid connection: grid-connected and island. The proposed system performance was compared against a fixed optimal settings protection system performance. The results showed that the proposed system presented better performance, allowing more speed and lower risk of discoordination for the protection system.